Pentingnya Penanaman Nilai-Nilai Agama Pada Pendidikan Anak Usia Dini Dalam Perspektif Al-Quran - Atin Risnawati; Dian Eka Priyantoro (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
As an educator, he is obliged to be able to create a righteous and righteous generation in accordance with religious values in accordance with. Early childhood education (ECE) is not only on the formal track, but the family and the surrounding environment also provide education for a child. This development of has the Koran as a source of law and science. Apart from that, the Koran also serves as a guideline for living in child rearing. Therefore, the Al-Quran becomes an important guide in the learning process for early childhood in order to produce a superior Islamic generation in the midst of global competition. In this case the author tries to explain the importance of inculcating religious values from the perspective of the Koran in early childhood education. Because early age is the earliest and easiest age for the formation of children's character compared to when the child has reached adolescence. The method used by the author is library research, which explains the theory of children's education, and how to cultivate the values of the Koran from an early age.Keywords: Early childhood education (ECE), Islamic Values, Quranic Perspective References Alia, T. (2018). Pendampingan Orang Tua pada Anak Usia Dini dalam Penggunaan Teknologi Digital. A Journal of Language, Literature, Culture and Education, 14(1), 65–78. Anggi, F. (2018). Pendidikan Karakter Prespektif Al-Quran Hadits. Ta"Lim, 1(2), 258–287. Ariyanti, T. (2016). Pentingnya Pendidikan Anak Usia Dini Bagi Tumbuh Kembang Anak. Jurnal Dinamika Pendidikan Dasar, 8(1), 50–58.Bahri, S. (2019). Urgensi Strategi Pembelajaran Karakter Pada Anak Usia Dini. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 4(2), 75–86. Damayanti, E., & Nasrul, M. A. (2020). Capaian Perkembangan Fisik Motorik Dan Stimulasinya Pada Anak Usia 3-4 Tahun. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2), 67–80. Departemen Agama RI. (2007). Al-Qur’an dan Tafsirnya (edisi yang disempurnakan) (Jilid VII.). Departemen Agama RI. Hafiz, A., & noor, hasni. (2015). Pendidikan Anak dalam Perspektif Alquran. Muallimuna (jurnal madrasah ibtidaiyah), vol, 1. No, 1–12. Halim, M. N. A. (2001). anak shaleh dambaan keluarga. Mitra Pustaka. Hasan, A. H. (2019). Tafsir Surat Luqman ayat 18 dan 19 (Tuntunan Akhlaq dan Keutamaannya). Kuliah Masjid Al-Mukhlisin Alam Damai. Hasbullah, H. (2018). Karekteristik Pendidikan Islam Menurut Imam Al-Ghazali Proses Pendidikan Islam Yang Berkelanjutan Dan Berangsur-Angsur. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 2(2), 85–93. Hidayat, B. (2017). Pembelajaran Alquran pada Anak Usia Dini Menurut Psikologi Agama dan Neurosains. Proceedings of The 2nd Annual Conference on Islamic Early Childhood Education, 2, 60. Hisyam, M. R., Suyanto, Sadzili, M., Arifin, Z., & Rahman, A. S. (2019). Peran Anggota Keluarga Berketahanan Dalam Perspektif Quran. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 9(2), 171–186.Imroatun, I., Nirmala, I., Juhri, J., & Muqdamien, B. (2020). Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(1), 57–66. Jahja, Y. (2011). Psikologi Perkembangan (cetakan 1). Prenada Media Group. JavanLabs. (2015). Surat Az-Zariyat Ayat 56. TafsirQ.com. Peraturan Menteri Pendidikan dan Kebudayaan Nomor 137 Tahun 2014 Tentang Standar Nasional Pendidikan Anak Usia Dini, (2014). Kementerian Agama RI. (2012). Al-Qur’an dan Terjemahnya. PT.Sinergi Pustaka Indonesia.Mertayasa, I. W., & Sudarsana, I. K. (2018). Pendidikan Karakter untuk AUD | 1. Jayapangus Press. Nadjih, D., & Imroatun, I. (2016). Hadits Tentang Pendidikan Jasmani Anak Usia Dini. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 51–64.Nugraha, E. (2020). Implementasi Program Tahfizh Qur’an Di PAUD Inklusif Dengan Model HOTS. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2), 95–106.Nugroho, T. (2014). Pendidikan Karakter Dalam Al-Qur’an (Studi Tafsir Pendidikan Surat Luqman). Ulumuddin Jurnal Ilmu-ilmu Keislaman, 4(1), 14–22. Nuraeni, Y. (2011). konsep dasar pendidikan anak usia dini. indeks. Nurhayati, E. (2016). Penanaman Nilai Keislaman ( Studi Kasus di RA Al-Ishlah Bobos - Cirebon ). Awlady, 1–22. Oktarianti, D. (2014). Konsep Pendidikan Aqidah Perspektif Islam (Studi Tafsir Tarbawi). Conciencia, 14(1), 105–127. https://doi.org/10.19109/ conciencia.v14i1.90 Raharjo, S. (2012). Penanaman Nilai-Nilai Agama Islam Pada Anak Usia Dini Di Kelompok Bermain Aisyiyah Al Husna Ii Pengasih, Kec. Pengasih, Kab. Kulon Progo. In Universitas Negeri Yogyakarta. Universitas Negeri Yogyakarta. Rahayu, S. H., Haroen, H., Budiutomo, T., Khasanah, N., & Nuryati, N. (2020). Manajemen Mutu Layanan Ta’lim Quran lil Aulad (TQA) di Yayasan Team Tadarus “AMM” Yogyakarta. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(2), 117–130. https://doi.org/10.47200/jnajpm.v5i2.578Rahayu, S. H., Huda, H., Wahono, J., Nadjih, D., & Sarnoto, A. Z. (2019). Implementasi Pendidikan Quran Tingkat Lanjut Bagi Santri Usia Dewasa. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 4(1), 63–78. https://doi.org/10.47200/jnajpm.v4i1.508